(untitled) (Research, Society and Development, 2020)
Linking the competences to the management methodologies is an urgency for the public service. In this sense, this article aimed to analyze the construction of processes for the implementation of competency management (GC) at the Federal University of Santa Maria (UFSM). For that, an exploratory-descriptive, qualitative and applied field research was carried out. Data were collected through nine semi-structured individual interviews and documentary analysis. The analysis took place through the Content Analysis Technique. The results showed that the UFSM has defined and is currently carrying out three main steps for the implementation of the GC: the sensitization of the servers, the identification of organizational competencies and the mapping of individual competencies. Were listed as challenges/difficulties of the process: lack of exclusive dedication of the GC Commission to the activities; the fact that it is a new and complex model in the public service; sensitization; reduced staff; high volume of work; resistance of servers; and doubts about the support of managers. It was discussed how the process is taking place in the University and were listed guidelines so that the GC is implemented in the best possible way in the Institution.